Congenital heart disease and thyroid dysfunction in Down syndrome reported at Children`s Hospital, Lahore, Pakistan - Muhammad Yaqoob; Jaida Manzoor; Syed Najam Hyder; Masood Sadiq (The Turkish Journal of Pediatrics)
Down syndrome is one of the main causes of intellectual disability in children. It occurs in every community and ethnic group. Several co-morbid conditions are associated with this syndrome. The present study was conducted to determine the frequency of congenital heart disease and thyroid dysfunction in a group of children affected with this genetic disorder. It was a record based retrospective study. A child having specific clinical features and chromosomal analysis showing an extra chromosome 21 was diagnosed as having Down syndrome. Diagnosis of congenital heart disease was based upon results of echocardiography. Thyroid dysfunction was diagnosed when either or both tetraiodothyronine and thyroid-stimulating hormone serum levels were abnormal. Three hundred and fifty cases were enrolled in the study according to the preset criteria for Down syndrome. Two hundred and ten (60%) were males and 140 (40%) females showing male to female ratio as 1.5 to 1. Majority of the children (55.1%) presented between 7 months and 24 months of age. Congenital heart defects were found in 41.8% of the cases. Ventricular septal defect was the most common, 41%. Thyroid dysfunction was found in 22% (n=60) of the cases of which 5.9% (n=16) had hypothyroidism. In conclusion, the frequency of congenital heart disease and thyroid dysfunction in Down syndrome children is high. Early referral of these children to tertiary health care facilities is emphasized as timely detection and management of these comorbid conditions will help in reducing the morbidity and mortality in this group of children.